Preparation and modification of novel phase change material Na2SO4·10H2O-Na2HPO4·12H2O binary eutectic hydrate salt. Issue 1 (31st March 2022) - Xin, Wang; Fang, Jianhua; Jiang, Wu; Ping, Liu; Na, Liu; Yanhan, Feng; Wang, Lin
ABSTRACT: A novel composite phase change material was prepared by compounding Na2 SO4 10H2 O-Na2 HPO4 12H2 O binary eutectic hydrate salt (BEHS) and modifying it. The optimum ratio of nucleating agent (nanometer AlN, borax) and thickening agent (hydroxyethyl cellulose, sodium alginate and sodium polyacrylate) was determined by uniform design test, so as to eliminate phase separation and reduce supercooling degree of BEHS. The prepared composite BEHS was microscopically analyzed by scanning electron microscopy (SEM) and X-ray energy spectroscopy (EDS) and its thermal stability of the composite BEHS was analyzed by melt-freezing cycle and Fourier transform infrared spectroscopy (FTIR). The results showed that the best composite BEHS was prepared by adding 1.8wt% nano-AlN, 1.5wt% borax, 4.8wt% hydroxyethyl cellulose, 4wt% sodium alginate and 1.5wt% sodium polyacrylate in the 80%Na2 SO4 10H2 O-20% Na2 HPO4 12H2 O system, which subcooling degree was 3.1°C, and phase change enthalpy was 180.2J/g. After 50 times and 100 times of melt-freeze cycle experiments, the phase change enthalpy of composite BEHS decreased by 2.72% and 3.61% respectively, and the material composition remains unchanged, the thermal properties are relatively stable